Cp-Free Cobalt-Catalyzed C–H Activation/Annulations by Traceless N,O‑Bidentate Directing Group: Access to Isoquinolines - Li, Xiao-Cai; Du, Cong; Zhang, He; Niu, Jun-Long; Song, Mao-Ping (Organic letters, 2019)
N,O-Bidentate directing-enabled, traceless heterocycle synthesis is described via Cp*-free cobalt-catalyzed C–H activation/annulation. The weakly coordinating nature of the carboxylic acid was employed for the preparation of isoquinolines. Meanwhile, the N–O bond of the α-imino-oxy acid can serve as an internal oxidant. Terminal as well as internal alkynes can be efficiently applied to the catalytic system. This operationally simple approach shows a broad substrate scope with the products obtained in good to excellent yields.